Genetic and Epigenetic Characteristics of Autosomal Dominant Pseudohypoparathyroidism Type 1B: Case Reports and Literature Review - Luo, Dandan; Qi, Xiangyu; Liu, Luna; Su, Yu; Fang, Li; Guan, Qingbo (Hormone and Metabolic Research, 2021)
Autosomal dominant pseudohypoparathyroidism 1B (AD-PHP1B) is a rare endocrine and imprinted disorder. The objective of this study is to clarify the imprinted regulation of the guanine nucleotide binding-protein α-stimulating activity polypeptide 1 (GNAS) cluster in the occurrence and development of AD-PHP1B based on animal and clinical patient studies. The methylation-specific multiples ligation-dependent probe amplification (MS-MLPA) was conducted to detect the copy number variation in syntaxin-16 (STX16) gene and methylation status of the GNAS differentially methylated regions (DMRs). Long-range PCR was used to confirm deletion at STX16 gene. In the first family, DNA analysis of the proband and proband’s mother revealed an isolated loss of methylation (LOM) at exon A/B and a 3.0 kb STX16 deletion. The patient’s healthy grandmother had the 3.0 kb STX16 deletion but no epigenetic abnormality. The patient’s healthy maternal aunt showed no genetic or epigenetic abnormality. In the second family, the analysis of long-range PCR revealed the 3.0 kb STX16 deletion for the proband but not her children. In this study, 3.0 kb STX16 deletion causes isolated LOM at exon A/B in two families, which is the most common genetic mutation of AD-PHP1B. The deletion involving NESP55 or AS or genomic rearrangements of GNAS can also result in AD-PHP1B, but it's rare. LOM at exon A/B DMR is prerequisite methylation defect of AD-PHP1B. STX16 and NESP55 directly control the imprinting at exon A/B, while AS controls the imprinting at exon A/B by regulating the transcriptional level of NESP55.
Keywords: autosomal dominant pseudohypoparathyroidism 1B; GNAS cluster; syntaxin-16; epigenetics